Gastrodin extends the lifespan of Caenorhabditis elegans via the DAF-16/FOXO signaling pathway and autophagy - Bo Li; Shan Li; Haoling Chen; Dan Wu; Xingwang Cao; Mingyue Yao; Shiying Xiong; Wei Meng; Li Dong (Functional & Integrative Genomics, 2026)

Molecular-level transformation of algal organic matter during water treatment processes by FT-ICR MS integrated with reactomics and interpretable machine learning - Wenke Li; Qiguang Shan; Qinglong Fu; Jibao Liu; Mahmoud Nasr; Huiyu Dong; Eunsang Kwon; Manabu Fujii (Water Research, 2026)

Late Neoarchean garnet-biotite gneiss widely distributed in the Wulashan area, northwestern North China Craton: Implications for the late Neoarchean tectonic environment and the origin of ca. 2.45 Ga metamorphic zircons - Daomao Huang; Hangqiang Xie; Shuguang Li; Pengchuan Li; Shoujie Liu; Shan Ke; Chunyan Dong; Yusheng Wan (Lithos, 2026)

Flow characteristics and precession performance of a fluid momentum wheel under different flow conditioning schemes - Ke-Dong Zhang; Hong-Yuan Li; Wen-Hua Wang; Shan Gao; Xiu-Di Ren; Bin Wang (Ocean Engineering, 2026)

Chemical and sensory profiling of fermented, washed, and artificially flavored coffee beans: Insights into flavour quality, authenticity, and food safety implications - Shengjie Duan; Jinya Dong; Shan Liu; Lihui Yu; Yanan Li; Huajie Yin; Chongye Fang; Zezhu Du; Yuanfeng Chen; Siyu Zhou; Chen Gong; Qiyuan Zhang; et al. (Food Chemistry, 2026)

HiMA-seq enables cost-effective spatiotemporal transcriptomics with high sensitivity and flexible multiplexity - Jiahe Liu; Zhidong Tang; Shan Jiang; Peiqing Miao; Shimei Yin; Ziwei Zhou; Li Lei; Dong Cheng; Xiru Liu; Liuyang Zhao; Ailong Huang (Chemical Engineering Journal, 2026)

Spatial distribution and compositional profile of microplastics in oil and gas extraction solid wastes: An overlooked source of microplastics - Yongxu Jin; Jianqi Dai; Xiang Wang; Shan Zhong; Yingzhou Huang; Xudong Mei; Shijie Wang; Min Hao; Jinwei Fang; Yunmin Zeng; Dong Li (Chemical Engineering Journal, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Ion-shielded emulsions enabling salt stability and synergistic pH-responsive release for high-salinity food preservation - Peng Shan; Jian Du; Zhihang Xu; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Jijuan Cao; Dong Lv; Haisong Wang (Food Packaging and Shelf Life, 2026)

Screening of immune adjuvants for an attenuated live vaccine derived from the Aeromonas veronii TH0426 strain with a hisJ gene deletion and evaluation of its immune protection in crucian carp - Qixing Huang; Ruitong Li; Shuoyu Wang; Ruiqi Liang; Peiqi Lu; Bingmei Du; Yan Cheng; Xiaochen Ren; Jinhong Li; Xu Dong; Jiaojiao Yang; Luyao Chu; et al. (Fish & Shellfish Immunology, 2026)

Source- and land-use-dependent controls on black carbon accumulation in urban soils: A comparison between an industrial city and a megacity in central China - Changlin Zhan; Shan Liu; Wei Kang; Min Guo; Tianpeng Hu; Yao Mao; Dong Li (Environmental Pollution, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Retraction notice to “Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China” [Sci. Total Environ. 898 (2023) 165303] - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2026)

Fusarielins Q–Y: fusarielin polyketides from Fusarium asiaticum QA-6 inhabiting the roots of the cultivated Artemisia argyi and their antibacterial activity against aquatic pathogens - Xiao-Shan Shi; Sui-Qun Yang; Yu-Liang Dong; Xiao-Ming Li; Ling-Hong Meng; Yan-He Li; Dun-Jia Wang; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2026)

Contrasting responses of soil-microbial-plant systems to co-application of biochar and microplastics with/without additives in acidic versus slightly alkaline heavy metal-affected soils - Jun Meng; Chaowen Yao; Chengmei Diao; Shibing Jia; Zhangtao Li; Jun Xu; Yan Xu; Dong Yang; Shengdao Shan; Huaihai Chen (Environmental Research, 2026)

A single-cell transcriptomic atlas of the spotted scat testis reveals two Sertoli cell subclusters with differential dmrt1Y expression - Yu Li; Mou-Yan Jiang; Shan-Ni Cao; You-Xing Peng; Yuan-Qing Huang; Hong-Juan Shi; Hua-Pu Chen; Tian-Li Wu; Dong-Neng Jiang (Aquaculture, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Red Monascus pigments attenuate fructose-driven bovine serum albumin (BSA) glycation via non-covalent and covalent interactions with proteins - Shufen Wu; Chengru Zhao; Xinxin Ma; Jingjie Cai; Changyan Dong; Shan Zhao; Zhongli Yan; Benxu Yang; Chao Li; Mianhua Chen; Changlu Wang (Food Chemistry, 2026)

In-situ decoupling spin-mediated hot carrier dynamics in MnO2/ZnS and tunable photocatalytic overall water splitting - Yinjun Zhang; Guoliang Zhu; Bo Li; Xinxin Jin; Lianwei Shan; Limin Dong (Chemical Engineering Journal, 2026)

Coupling near infrared spectroscopy with machine learning algorithms for simultaneously detecting multiple microplastics in soil - Jia Long; Xi Li; Renjie Yang; Guimei Dong; Yaping Yu; Huiyong Shan (Journal of Soils and Sediments, 2026)

Coal Burst Failure and Probabilistic Early Warning for Combined Coal–Rock Based on Electric Potential Under True Triaxial Stress - Tiancheng Shan; Zhonghui Li; Nan Li; Enyuan Wang; Yue Niu; Dong Chen; Shan Yin; Haishan Jia; Mohamed Elgharib Gomah (Rock Mechanics and Rock Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Study on the effect of pulsed electric field on the enhancement of aerobic granular sludge formation and performance by inhibiting the growth of filamentous bacteria - Liang Li; Liying Fei; Tong Zhu; Zhuang Shan; Yihua Dong; Guangsheng Qian (Journal of Water Process Engineering, 2026)

Coupling between mobile genetic elements and potential sulfur cycling microorganisms is associated with antibiotic resistance gene distribution in coastal sediments - Li Chen; Diantao Ping; Danyu Zheng; Shan Zhou; Chaoyue Zhang; Qi Chen; Xiaohui Wang; Xuri Dong; Lixin Zhu (Journal of Environmental Chemical Engineering, 2026)

Valorization of phosphogypsum and municipal sludge into functional ceramic filter for closing the loop in the phosphorus chemical industry: A sustainable "waste-treats-waste" strategy - Shuaicheng Huang; Zebing Zhu; Lili Shan; Zhuye Ni; Xiaoni Li; Jingliang Dong; Changlong Pang (Journal of Cleaner Production, 2026)

Hydrophobic deep eutectic solvents for highly efficient n-hexane capture - Yan Zhao; Yanlong Xu; Anna Mei; Yingzhe Chen; Chee Sien Wong; Zhao Huang; Yulong Shan; Jianmeng Chen; Qian Li; Dong-Zhi Chen (Journal of Environmental Sciences, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

Colorimetric/fluorescent dual-module bivalent aptasensor for kanamycin detection based on silver nanoparticles and silver nanoclusters - Dong Xu; Xingxing Li; Xinxin Yan; Lei Shan; Fuhou Li; Weixia Wang; Yuchengmin Zhang; Jinri Chen (Food Control, 2026)

Thiosemicarbazide-functionalized graphene oxide as a novel adsorbent for ultrasensitive determination of trace Hg in water by TXRF - Bo Wang; Wenbao Jia; Dong Lao; Yiying Li; Kai Zeng; Yongsheng Ling; Qing Shan (Chemical Engineering Journal, 2026)

Mechanism of Prestress Loss in Anchor Cables Embedded in Two-Region Composite Rock Masses: Development and Analysis of a Coupled Model - Renliang Shan; Haobo Bai; Dong Liu; Hailong Wang; Mingyue Nie; Yongzhen Li; Peng Sun; Haotian Wu; Shengchao Xiao (Rock Mechanics and Rock Engineering, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

A food-grade antimicrobial peptide from Lactococcus lactis: A potent and stable bio-preservative against Gram-negative pathogens in orange juice - Mingyang Hu; Sina Cha; Yuwen Li; Lu Zhao; Yutong Xue; Chenyu Xue; Na Dong; Anshan Shan (Food Control, 2026)

Potential anti-glioma targets and mechanisms of Smilax china L. based on network pharmacological, molecular docking and experimental verification - Zhiyong Jin; Shan Jiang; Sicheng Ma; Sijie Dong; Changzhou Xiao; Liujie Yuan; Feifan Zhang; Mengyao Zhu; Gang Li; Rutong Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Regenerative treatment of aquatic pollutants of microplastic and antibiotics based on synergistic effect of magnetic biochar/protonated g-C3N4 - Zifeng Li; Rui Shan; Guoqiang Wei; Leyi Huang; Dong Liang; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

Mechanistic comparison of heavy metals migration and immobilization between fast/slow pyrolysis of textile dyeing sludge - Danni Li; Fengxiao Zhao; Dong Liang; Wenqi Guan; Hongyuan Chen; Rui Shan; Haoran Yuan; Yong Chen (Journal of Hazardous Materials, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Delayed disulfiram targeting GSDMD-NETs axis rescues sepsis by limiting bacterial spread and lung injury - Xiaoxi Shan; Zhishu Li; Lixia Dong (Inflammation Research, 2026)

Mechanistic insights into product distribution and bromine fixation during co-pyrolysis of cattle manure with organic components of printed circuit boards - Wenqi Guan; Dong Liang; Che Zhao; Danni Li; Shuxiao Wang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Water-assisted thermal polymerization synthesis of cobalt-doped porous g-C3N4/Ni2P composites for enhanced photocatalytic hydrogen evolution - Liqin Liu; Dan Li; Tianci Huang; Jian Li; Yanli Zhuang; Xinxin Jin; Lianwei Shan; Hao Sun; Limin Dong; Jie Yao (Fuel, 2026)

Montmorillonite-enhanced nitrogen fixation and emission reduction during food wast pyrolysis - Hongyuan Chen; Danni Li; Yazhuo Wang; Yaoxin Xiao; Dong Liang; Gangqi Cheng; Rui Shan; Haorang Yuan; Yong Chen (Fuel, 2026)

Investigation on Brazilian Failure Evolution and Electric Potential Response of Sandstone-Concrete Interface Through Multiple Nonlinear Statistical Approaches - Tiancheng Shan; Zhonghui Li; Enyuan Wang; Xin Zhang; Haishan Jia; Yunpeng Zhang; Yue Niu; Dong Chen (Rock Mechanics and Rock Engineering, 2026)

Identification of stomatal opening positive regulators in augustinegrass - Dong-Li Hao; Jia Qu; Jun-Qin Zong; Zhi-Yong Wang; Jiang-Shan Hao; Hai-Long Lu; Ying Zhao; Dao-Jin Sun; Sheng-Nan Yang; Jian-Xiu Liu; Li Liao; Ling Li (Horticulture, Environment, and Biotechnology, 2026)

High-Resolution Fog Detection over a Mountainous Lake Basin - Haijun Li; Jiusheng Shan; Jiajie Xin; Xiangxiang Chen; Meng Dong; Xiao Xiao (Journal of Meteorological Research, 2026)

3-Methyladenine administration alleviates cognitive and memory dysfunction in attention-deficit/hyperactivity disorder by modulating autophagy - Ge-Ge Lv; Yu-Dong Shan; Jing-Jing Shao; Cao-Yuan Ma; Zhi-Fang Yu; Ji-Zhen Liu; Li-Min Zhang; Wei Zhang (Psychopharmacology, 2026)

High-linearity flash ADC achieved through design-technology co-optimization based on two-dimensional semiconductor - Xiangqi Dong; Yuxuan Zhu; Xiangyu Liu; Jieya Shang; Zhengjie Sun; Zhejia Zhang; Weijie Sun; Xinrong Shan; Haojie Chen; Jingde Xu; Saifei Gou; Jing Guo; et al. (Science Bulletin, 2026)

Enhancing free hydroxyl radical generation via noble metal-modified TiO₂ for efficient benzisothiazolinone degradation with reduced H₂O₂ consumption - Meng Xu; Xiao-qing Dong; Li-fang Chen; Ping Yu; Xin-yu Li; Shan-shan Lv; Ya-wen Qi; Wei Zhang; Peng Jiang; Xiao-long Zhou (Journal of Water Process Engineering, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Late Mesozoic exhumation of metamorphic core complexes from the Xiaoqinling to Dabie orogen, central China: a record of Paleo-Pacific slab rollback - Wan-Shan Lei; Yu Duan; Zhi-Qiang Liu; Ran Wang; Hai-Dong Zhang; San-Zhong Li (International Geology Review, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Toonasinetins A and B, two new compounds from the branches and leaves of Toona sinensis - Nai-Dong Li; Cheng-Shan Wei; Chun-Xia Song; Chun-Jiang Du; Juan Xu (Phytochemistry Letters, 2025)

Self-assembled carrier-free nanoplatforms for sequential modulation of the oxidative-inflammatory cascade in cerebral ischemia-reperfusion injury - Lu Lu; Xianru Bi; Meihua Shan; Dong Liu; Mingzhen Yang; Xia Li; Jiqin Lian; Chunyu Zeng (Chemical Engineering Journal, 2025)

Cellular and molecular targets in β-Thalassemia: advances in iron Regulation, Erythropoiesis, and Gene-Based therapies - Xueting Shan; Qianlian Li; Meijuan Wang; Yifan Niu; Zhongxin Sun; Xiang Ma; Tao Wang; Xiangmin Tong; Jufang Zhang; Dong Niu (Functional & Integrative Genomics, 2025)

Roles of Immunity and Endogenous Retroelements in the Pathogenesis of Rheumatoid Arthritis and Treatment Strategies - Mingyang Li; Yuanyuan Sun; Xueting Shan; Yuhong Tong; Yite Fu; Xiang Ma; Zhongxin Sun; Yun Xiang; Yidan Zhu; Tao Wang; Xin Wang; Jufang Zhang; et al. (Functional & Integrative Genomics, 2025)

Autoimmune mechanisms and inflammation in obesity-associated type 2 diabetes, atherosclerosis, and non-alcoholic fatty liver disease - Yuanyuan Sun; Xueting Shan; Mingyang Li; Yifan Niu; Zhongxin Sun; Xiang Ma; Tao Wang; Jufang Zhang; Dong Niu (Functional & Integrative Genomics, 2025)

Oxidative stress and ferroptosis in diabetic cardiomyopathy: mechanistic interplay and therapeutic implications - Shan Li; Yuhe Shu; Shuyu Yang; Simin Zhang; Haoling Chen; Dan Wu; Bo Li; Li Dong (Apoptosis, 2025)

Microbial synergistic corrosion of Ti30ZrAlV alloy: Acid dissolution-electron transfer coupling mechanism - Zhihao Feng; Yu Zhao; Qian Feng; Kaimin Wei; Huicong Dong; Shan Liu; Jiangang Wang; Guang Chen; Jianhui Li (Process Safety and Environmental Protection, 2025)

Outbreeding of isofemale lines as a candidate approach to improve the quality of thelytokous Wolbachia-infected line of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae - Hong-Yu Liang; Ying Shan; Qian-Jin Dong; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Invertebrate Pathology, 2025)

Development of a rapid method for the determination of the spatial distribution of protein in wheat grain using mature resin section and image processing algorithm - Hengtong Wang; Haijiang Min; Minghao Gao; Han Zhong; Chuan Zhong; Zenan Ban; Qin Zhou; Xiao Wang; Jian Cai; Qing Li; Mei Huang; Dong Jiang; et al. (Journal of Cereal Science, 2025)

Spontaneously oriented receding on superhydrophobic bundles for high-efficiency enrichment of airborne microdroplets - Shan Peng; Peibin Liang; Mingzhan Wang; Zhao Li; Huanhuan Dong; Xueji Zhang; Hubao A; Shuang Zheng; Yuanyuan Zhao (Chemical Engineering Journal, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

Retraction Note to: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2025)

Sulfur-induced electron migration in thin-layered Bi2MoO6 triggers 1O2-dominated pathway for selective NO photoconversion - Hongjing Liu; Shan Ren; Xiaodi Li; Qingqing Zhou; Yao Yang; Peng Chen; Shouning Chai; Chi He; Bofeng Bai; Fan Dong (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Multi-dimensional decoupling local electron spin and inner Helmholtz layer roles in MoS2/MoSe2 superlattice photocatalysts - Guoliang Zhu; Jagadeesh Suriyaprakash; Guangri Chen; Dapeng Hong; Jiajun Gu; Yanyang Zhang; Lianwei Shan; Huanyan Xu; Xuejiao Li; Haitao Wu; Limin Dong; Shuyan Qi; et al. (Chemical Engineering Journal, 2025)

Research on seismic resilience evaluation method of RC frame structures - Yong-Ming Li; Shan-Suo Zheng; Li-Guo Dong; Song Yang (Bulletin of Earthquake Engineering, 2025)

Identification and Analysis of Potential Biomarkers Associated with Neutrophil Extracellular Traps in Cervicitis - Wantao Liang; Yanyuan Bai; Hua Zhang; Yan Mo; Xiufang Li; Junming Huang; Yangliu Lei; Fangping Gao; Mengmeng Dong; Shan Li; Juan Liang (Biochemical Genetics, 2025)

In vitro culture and comparative pathogenic characteristics of two ciliates prevalent in the sea cucumber Apostichopus japonicus - Dongmei Yue; Peipei Li; Jingwei Jiang; Ying Dong; Bai Wang; Shan Gao; Gang Song; Hongjuan Sun; Feifei Zhang; Pingzhe Jiang; Yongjia Pan; Zunchun Zhou (Aquaculture, 2025)

Toxicity of 6PPD to the stony coral Pocillopora damicornis in different developmental stages - Bing Yang; Qingsong Yang; Junde Dong; Jie Li; Shan Liu; Ying Zhang; Huiming Sun; Chang Chen; Juan Ling (Journal of Hazardous Materials, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Reactivation mechanism of loess-mudstone historical landslide under rainfall-vibration effects - Haoyu Dong; Jiading Wang; Lin Li; Dengfei Zhang; Zailiang Xu; Kai Han; Shan Li; Lirong Qi (Engineering Geology, 2025)

Rationally designed and facilely constructed CoFe2O4@SiO2 yolk@shell heterostructure spherical jars as interlayer achieve high-performance Li S batteries via “3 + 1” modal anchoring & catalyzing coupled with microreactor - Yingying Bao; Bin Yue; Lin Li; Shan Jiang; Hong Shao; Yunrui Xie; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

Mutation in maize chloroplastic polypeptide chain release factor (ZmcpRF1) affects chloroplast development and leaf color - Hao Chen; Haixiao Dong; Xiaohui Shan; Yuan Jiang; Shipeng Li; Hongkui Liu; Shengzhong Su; Yaping Yuan (Planta, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Dual associations of post-sleep and pre-wake light-at-night (LAN) exposure with myopia in children and adolescents - Di Shi; Jiaxin Li; Jiajia Dang; Yunfei Liu; Ziyue Chen; Yaqi Wang; Jieyu Liu; Xinxin Wang; Shan Cai; Yihang Zhang; Tianyu Huang; Haihua Chen; et al. (Environmental Research, 2025)

Eccentric compressive performance of H-shaped steel-reinforced geopolymer recycled aggregate concrete-filled GFRP tube columns - Dongming Huang; Dong Zhao; Zhenzhen Liu; Yiyan Lu; Shan Li (Engineering Structures, 2025)

Research progress of high-strength self-healing polymer materials: Balance between mechanical strength and self-healing efficiency - Zhi-Hui Yan; Hua-Xin Huang; Guo-Quan Ding; Shan-Shan Dong; Ke-Jin Jiang; Yu-Ying Li; Yang Liu; Yan Jiang; Shuang-Fei Wang; Guo-Hua Hu; Jun Du; Shi-Xian Zhang; et al. (Chemical Engineering Journal, 2025)

Analysis of Sensory Qualities and Microbial Community Structure in the Fermented Grains by Low-Temperature Daqu from Different Regions of China - Fanshu Xiang; Wenchao Cai; Qiangchuan Hou; Zhongjun Liu; Liang Li; Xiaoyuan Dong; Chunhui Shan; Zhuang Guo (Current Microbiology, 2025)

Design and test of a rotary centrifugal granular fertiliser hole-applied discharge device - Xinhe Shan; Liwei Li; Bingxin Yan; Jianjun Dong; Xueli Wei; Zhijun Meng; Guangwei Wu (Biosystems Engineering, 2025)

Mass spectrometry-based lipidomics combined with flavoromics reveal the mechanism of characteristic flavor formation in Chelidonichthys kumu bone soup treated with different edible oils by frying - Zixi Li; Meng Dong; Libo Qi; Shan Shang; Yan Guo; Lei Qin; Baoshang Fu (Food Bioscience, 2025)

Dual protection against grouper Rana-Iridovirus (GIV-R) and nervous necrosis virus (NNV) by novel GIV-R-Δ51−NNV-CP chimeric vaccine candidates - Shan Ding; Yong Li; Qianqian Sun; Zhiming Zhu; Fangzhao Yu; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Harnessing the MYB51/SWEET20 module to increase soybean yield by facilitating sugar supply to sink organs - Jiafang Shen; Dong Cao; Songli Yuan; Qingnan Hao; Hongli Yang; Yi Huang; Lihong He; Jialing Yuan; Zhonglu Yang; Shuilian Chen; Zhihui Shan; Wei Guo; et al. (Plant Cell Reports, 2025)

Waste-modified asphalt for climate change mitigation: Carbon and pollution reduction - Zejiao Dong; Lingwen Li; Tao Zhou; Hu Yang; Liping Cao; Liyan Shan (Transportation Research Part D: Transport and Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

Waste utilization to construct highly stable and rapid photothermal superwetting textiles for efficient separation of viscous oil/water mixture - Huanhuan Dong; Junxiang Guo; Zhao Li; Xiaoyu Ji; Shan Peng (Journal of Environmental Chemical Engineering, 2025)

A fluorescent aptasensor for kanamycin detection in milk, seafood and water samples using DNA-AgNCs and exonuclease I-assisted recycling amplification strategy - Dong Xu; Lei Shan; Bei Guo; Jing Wang; Qiang Huang; Shujun Wang; Fuhou Li; Shaojie Wu; Weixia Wang; Jinri Chen (Food Chemistry, 2025)

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

An Improved Slip Circle Method for Evaluating the Stability of Submarine Landslides under Wave Loading - Miaojun Sun; Zhigang Shan; Changdong Li; Jiaqing Zhou; Qingbing Liu; Xinji Zou; Qilong Li; Biwen Dong (Journal of Earth Science, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Mycoplasma ovipnuemoniae impairs the immune response of sheep and suppresses neutrophil function by inhibiting S100A9 - Chenbo Yan; Tianning Dong; Yiyi Shan; Bingru Zhao; Hua Yang; Yu Cai; Shanglai Li; Qiuyue Liu; Yuefeng Chu; Huafang Hao; Zilong Cheng; Maojun Liu; et al. (Veterinary Microbiology, 2025)

The MdWRKY17 positively regulates nitrate uptake by promoting MdNRT2.5 expression under long-term low N stress in apple - Zehui Hu; Dongqian Shan; Chanyu Wang; Yixue Bai; Tianci Yan; Tong Zhang; Handong Song; Ruoxue Li; Yixuan Zhao; Qian Deng; Changjian Dai; Peiyun Xiao; et al. (Plant Science, 2025)

Three-year remediation evaluation for arsenic and cadmium co-contaminated acidic and alkaline paddy fields: Insights on availability, bioaccumulation, health risk, and cost - Jian Liu; Xiangxue Xu; Jun Meng; Zhangtao Li; Ye Wu; Linling Xu; Ghulam Haider; Dong Yang; Shengdao Shan (Journal of Environmental Chemical Engineering, 2025)

Protosappanin B activates the Wnt pathway to protect against glucocorticoid-induced osteoblast inhibition and enhance bone formation - Jigeng Fan; Yahui Wang; Houzhi Yang; Shaoyuan Huang; Yuan Ma; Jie Guo; YuTao Jia; Ying Zhang; Yonggang Fan; Donglun Xiao; Jiawei Zhang; Jianwei Li; et al. (Chemico-Biological Interactions, 2025)

Ground straw mulching level classification based on a terral grid system and deep learning - Shan Jiang; Hongwen Li; Zhao Zhang; Kaidong Liu; Caiyun Lu; Chao Wang; Chayan Kumer Saha; Rongrong Li; Zhengyang Wu; Zongfu Yang; Dong He (Computers and Electronics in Agriculture, 2025)

ADAMTS13 attenuates renal fibrosis by suppressing thrombospondin 1 mediated TGF-β1/Smad3 activation - Jie Guo; Suhan Zhou; Honghong Wang; Xingyu Qiu; Fang Dong; Shan Jiang; Nan Xu; Yu Cui; Ruisheng Liu; Pengyun Li; Zufu Ma; Liang Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Renewable intelligent superwetting biomass-based catalyst for harmless degradation of neonicotinoids with different polarities - Ruimeng Han; Shan Peng; Chunfang Zhang; Lei Wang; Xiaoyu Ji; Huanhuan Dong; Lianshan Li; Xiaoxin Chen (Journal of Cleaner Production, 2025)

Phase transition kinetics and mass transfer characteristics of CO2 hydrate formation process under geological storage conditions: A comprehensive review - Xuemin Zhang; Hongbin Song; Wenxin Dong; Xinying Lan; Tao Shan; Jinping Li; Huan Sun; Wenqiang Cui; Qingbai Wu (Journal of Cleaner Production, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhancing NH3-SCR denitrification performance through synergistic A- and B-site effects via CeFe modification of LaMnO3 - Wei Zhang; Qiao Wu; Mengyao Dong; Kang Xie; Yanshan Yin; Yunhe Zhou; Jie Li; Yehao Fu; Yaocheng Liang; Quanbin Song; Min Ruan; Shan Cheng; et al. (Fuel, 2025)

Peficitinib suppresses diffuse-type tenosynovial giant cell tumor by targeting TYK2 and JAK/STAT signaling - Shan Lu; Chenxi Cao; Wenjia Zhang; Jiayi Li; Jingli Yang; Zisheng Huang; Zhijun Wu; Baitao Liu; Hongjie Huang; Haijun Wang; Yongjian Wang; Dingge Liu; et al. (Science China Life Sciences, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

Electroactive bacteria-established long-distance electron transfer to oxygen facilitates bio-transformation of dissolved organic matter for sediment remediation - Yinxiu Liang; Meijun Dong; Shan Yang; Lizhou Lin; Haobin Huang; Daobo Li; Min Ji; Meiying Xu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Failure evolution and precursor prediction of fissured sandstone based on power-law behavior of electric potential - Tiancheng Shan; Zhonghui Li; Enyuan Wang; Xin Zhang; Haishan Jia; Xiaoran Wang; Enlai Zhao; Yue Niu; Dong Chen (Engineering Geology, 2025)

OCTN2 expression and function in the Sertoli cells of testes from patients with non-obstructive azoospermia - Dong Li; Nan Jiang; Minjia Pan; Linzi Ma; Yunchong Huang; Xiaoheng Xu; Xinyan Yang; Yongtong Zhu; Hua Shi; Shan-Chao Zhao (Journal of Molecular Histology, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Detoxification effect of sodium thiosulfate on cadmium poisoning in Litopenaeus vannamei and the mechanisms of intestinal flora regulation - Shan Gao; Danqing Hou; Xuejie Wang; Jianbo Yu; Jiaxin Dong; Ting Li; Chengbo Sun (Marine Pollution Bulletin, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Polyol-assisted ternary deep eutectic solvent protective lignocellulose pretreatment for high-efficiency xylan utilization and ethanol production - Shan Li; Yang Wang; Qinghe Dong; Zitong Yuan; Tiancheng Mu; Zhimin Xue; Limin Cao (Carbohydrate Polymers, 2024)

Decadal trends of black carbon and heavy metal accumulation in a lake sediment core from central China: A historical perspective - Changlin Zhan; Dejun Wan; Yongming Han; Jiaquan Zhang; Shan Liu; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao; Dong Li (CATENA, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Optimization of kW-scale methanol reforming high-temperature proton exchange membrane fuel cells with efficient waste heat utilization - Ruhang Zhang; Hongxiang Zheng; Chuandong Li; Feng Huang; Xinhai Yu; Shan-dong Tu (Fuel, 2024)

Pyrrole adducts mediated mitochondrial dysfunction activates SARM1-dependent axon degeneration in 2,5-hexanedione-induced neuropathy - Wenting Ni; Yihan Ye; Shuai Wang; Xianjie Li; Hui Li; Dong Cheng; Qiang Jia; Zhidan Liu; Shulin Shan; Yalong Qiang; Shihua Chao; Xiulan Zhao; et al. (Environmental Pollution, 2024)

Effects of hydrothermal pretreatment on sulfadiazine degradation during two-stage anaerobic digestion of pig manure - Shupeng Lin; Yitao Li; Chunchun Guo; Liangcheng Yang; Yanfang Ma; Renjie Dong; Shan Liu (Chemosphere, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Unravelling the influence of microplastics with/without additives on radish (Raphanus sativus) and microbiota in two agricultural soils differing in pH - Jun Meng; Chengmei Diao; Zhonghua Cui; Zhangtao Li; Jiayi Zhao; Haibo Zhang; Minjun Hu; Jun Xu; Yugen Jiang; Ghulam Haider; Dong Yang; Shengdao Shan; et al. (Journal of Hazardous Materials, 2024)

Identifying long-term health risks associated with environmental chemical incidents - Shan Niu; Zhaomin Dong; Li Li; Carla Ng (Journal of Hazardous Materials, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Electric potential of thermally damaged granite under compression shear loading: Response mechanism and precursor - Tiancheng Shan; Zhonghui Li; Xiaoran Wang; Xin Zhang; Enyuan Wang; Shuxin Liu; Haishan Jia; Yue Niu; Weichen Sun; Dong Chen; Qiming Zhang (Engineering Geology, 2024)

Mechanical-vibration-driven piezocatalytic degradation of organic pollutants over microcrystalline SnSe with selenium vacancies - Yue Liu; Huan-Yan Xu; Bo Li; Mao-Chang Cao; Li-Guo Jin; Lian-Wei Shan; Li-Min Dong (Chemical Engineering Journal, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

Exploring the influence of sulfadiazine-induced stress on antibiotic removal and transformation pathway using microalgae Chlorella sp. - Yanfang Ma; Shupeng Lin; Ting Guo; Chunchun Guo; Yitao Li; Yahan Hou; Yongchang Gao; Renjie Dong; Shan Liu (Environmental Research, 2024)

Efficient electrocatalytic OOH production on P–N–CuO for selective cleavage of lignin C–C bonds in the photoelectric collaborative system - Linglong Shi; Huifang Ma; Bin Shan; Da Li; Shuangzhen Guo; Yu Liu; Jianjie Wang; Weifang Dong; Mengqi Li; Shuting Gu; Weiyu Xia (Chemical Engineering Journal, 2024)

Spodumene nanosheets@ZrO2-SiO2 heterostructure nanofibers modified separator for long-cycle lithium-sulfur batteries - Lin Li; Bin Yue; Yingying Bao; Shan Jiang; Hong Shao; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Bio-H2 production enhancement from the NaOH-urine pretreated rice straw: The holocellulose retention yield promotion - Lili Dong; Geng Luo; Yu-Hao Wang; Wan-Qing Wang; Guang-Li Cao; Shan-Shan Yang; Fei Yang (Biomass and Bioenergy, 2024)

Dietary chitosan reversed the toxic effects of polystyrene microplastics on Nile tilapia (Oreochromis niloticus) liver by inhibiting mitochondrial damage - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Hua Wen; Shan Zhong; Yun-feng Li; Ming Jiang (Reviews in Fish Biology and Fisheries, 2024)

Novel design of simplified β-hairpin antimicrobial peptide as a potential food preservative based on Trp-pocket backbone - Changxuan Shao; Yuanmengxue Wang; Guoyu Li; Hongrui Guan; Yongjie Zhu; Licong Zhang; Na Dong; Anshan Shan (Food Chemistry, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Three new chromones from the whole plants of Chamaecrista rotundifolia and their anti-rotavirus activities - Pei-Song Yang; Xin-Yan He; Shan-Shan Li; De-Quan Huang; Si-Yu Shen; Xiao-Shan Liu; Yue-Yu Ma; Miao Dong; Min Zhou; Feng-Xian Yang; Yin-Ke Li (Natural Product Research, 2024)

Promoting effect and microscopic mechanism of train-induced vibration on loess disintegration - Shan Li; Jiading Wang; Kai Han; Li Wang; Dengfei Zhang; Haoyu Dong; Bo Cui (Engineering Geology, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Realizing high-efficiency thermoelectric module by suppressing donor-like effect and improving preferred orientation in n-type Bi2(Te, Se)3 - Yichen Li; Shulin Bai; Yi Wen; Zhe Zhao; Lei Wang; Shibo Liu; Junqing Zheng; Siqi Wang; Shan Liu; Dezheng Gao; Dongrui Liu; Yingcai Zhu; et al. (Science Bulletin, 2024)

Investigating the Constitutive Model of Frozen Supersulfate Saline Soil: Insights from Fractional Calculus - Sheng Li; Hongbo Li; Xinrui Kang; Long Shan; Zi Wang; Xuguang Dong; Libo Wu (Cold Regions Science and Technology, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

Analytical solution for the seismic response of a nearly saturated sloping seabed: Weak interlayer - Zhendong Shan; Zhinan Xie; Jinkai Li; Daosheng Ling; Rui Dong (Ocean Engineering, 2024)

Nondestructive prediction of lime acidity with a single scan using two types of near infrared spectrometers and ensemble learning strategy - Pao Li; Yiqing Dong; Liwen Jiang; Guorong Du; Yang Shan (Journal of Food Engineering, 2024)

Experimental study on response and precursor of pressure stimulated currents of combined coal-rock under cycling stress - Zhonghui Li; Tiancheng Shan; Enyuan Wang; Yue Niu; Xiaoran Wang; Xin Zhang; Haishan Jia; Dong Chen; Shan Yin; Weichen Sun (International Journal of Rock Mechanics and Mining Sciences, 2024)

A functional Pickering emulsion coating based on octadecenylsuccinic anhydride modified γ-cyclodextrin metal-organic frameworks for food preservation - Yannan Zhang; Dehai Yu; Rui Zhao; Zhuo Li; Baoting Dong; Feihong Hu; Shan Li; Fengshan Zhang; Huili Wang (Food Hydrocolloids, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Initiation mechanism of shallow loess slope sliding under coupling effect of train vibration and rainfall - Kai Han; Jiading Wang; Shan Li; Peng Xiao; Dengfei Zhang; Fei Wang; Haoyu Dong (Soil Dynamics and Earthquake Engineering, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Interaction mechanism and binding mode of phycocyanin to lysozyme: Molecular docking and molecular dynamics simulation - Ying Bai; Yingzhen Wang; Xiang Li; Jiarui Jin; Yujing Lu; Shan Jiang; Xiuping Dong; Hang Qi (Food Chemistry, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Nano‑selenium alleviates the pyroptosis of cardiovascular endothelial cells in chicken induced by decabromodiphenyl ether through ERS-TXNIP-NLRP3 pathway - Yangyang Jiang; Bowen Dong; Xing Jiao; Jianhua Shan; Cheng Fang; Kaixuan Zhang; Di Li; Chenchen Xu; Ziwei Zhang (Science of The Total Environment, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

Integrating the confinement effect and bimetallic cycles in a hierarchical Co3O4@Co3O4/Fe3O4 yolk-shell nanoreactor for peroxymonosulfate activation enhancement - Bo Li; Huan-Yan Xu; Gu-Hao-Nan Chi; Li-Min Dong; Lian-Wei Shan; Li-Guo Jin; Yan-Li Zhuang; Mao-Chang Cao; Xiu-Lan He; Shu-Yan Qi (Chemical Engineering Journal, 2024)

Retraction Note: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Preparation and properties of geopolymer containing phosphoric acid-activated fly ash and mechanically-milled kaolinite: Experiments and density function theory - Jiang-shan Li; Wei Zhang; Lei Lang; Chen-xi Dong; Kang Huang (Journal of Cleaner Production, 2024)

PhenoNet: A two-stage lightweight deep learning framework for real-time wheat phenophase classification - Ruinan Zhang; Shichao Jin; Yuanhao Zhang; Jingrong Zang; Yu Wang; Qing Li; Zhuangzhuang Sun; Xiao Wang; Qin Zhou; Jian Cai; Shan Xu; Yanjun Su; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Physicochemical properties of clayey deposits slurry treated by lime-activated ISSA and GGBS considering seawater salinity effect - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Jiang-Shan Li; Zhen-Yu Yin; Jian-Hua Yin; Yong-Gui Chen (Applied Clay Science, 2024)

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Fabrication of nanocomplexes for anthocyanins delivery by ovalbumin and differently dense sulphate half-ester polysaccharides nanocarriers: Enhanced stability, bio-accessibility, and antioxidant properties - Ruihong Dong; Ziyan Huang; Wenjie Ma; Qiang Yu; Jianhua Xie; Jinlong Tian; Bin Li; Jialuo Shan; Yi Chen (Food Chemistry, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Growth differentiation factor 7 pretreatment enhances the therapeutic capacity of bone marrow-derived mesenchymal stromal cells against cerebral ischemia-reperfusion injury - Hongmiao Tao; Lin Li; Lihua Dong; Haohao Chen; Xiaoyun Shan; Lujie Zhuge; Hongqiang Lou (Chemico-Biological Interactions, 2023)

Rapid Evaluation of Rock Mass Integrity of Engineering Slopes Using Three-Dimensional Laser Scanning - Liang Chen; Yunfeng Ge; Xuming Zeng; Haiyan Wang; Changdong Li; Shan Dong; Yang Ye; Dongming Gu (Journal of Earth Science, 2023)

RETRACTED: Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2023)

Discovery of Michael reaction acceptors from the leaves of Ailanthus altissima by a modified tactic - Zhi-Kang Duan; Shan-Shan Guo; Li Ye; Zhi-Heng Gao; Dai Liu; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

1-D coupled surface flow and transport equations revisited via the physics-informed neural network approach - Jie Niu; Wei Xu; Han Qiu; Shan Li; Feifei Dong (Journal of Hydrology, 2023)

Growth mechanism and uranium extraction from seawater and nuclear waste of densely packed single crystals almond Na2TiOSiO4 with controllable crystallization - Shan Pian; Guojun Dong; Youhong Xiao; Rumin Li; Yu Su (Journal of Environmental Chemical Engineering, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Trichlorfon blocks androgen synthesis and metabolism in rat immature Leydig cells - Huan Chen; Yaoyao Dong; Huitao Li; Zhili Chen; Ming Su; Qiqi Zhu; Ren-Shan Ge; Xinjun Miao (Reproductive Toxicology, 2023)

An efficient LSTM network for predicting the tailing and multi-peaked breakthrough curves - Jie Niu; Shan Li; Wei Xu; Feifei Dong; Fen Huang; Han Qiu (Journal of Hydrology, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Reduced dietary Ca, Cu, Zn, Mn, and Mg bioavailability but increased Fe bioavailability with polyethylene microplastic ingestion in a mouse model: Changes in intestinal permeability and gut metabolites - Shan Chen; Shi-Wei Li; Xue-Yuan Gu; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Science of The Total Environment, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Interleukin-16 genetic polymorphisms in Guangxi Chinese with hepatitis B virus-related liver cirrhosis - Xiaolian Zhang; Wenjun Tang; Xue Qin; Shan Li; Dong Liang (Molecular Biology Reports, 2023)

Loss of ndrg2 Function Is Involved in Notch Activation in Neuromast Hair Cell Regeneration in Zebrafish - Xin Wang; Xiaodong Gu; Cheng Wang; Yingzi He; Dong Liu; Shan Sun; Huawei Li (Molecular Neurobiology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

The risk factors associated with traumatic subdural effusion for patients with traumatic brain injury who did not undergo decompressive craniectomy - Xiangzhu Shen; Yafei Han; Haichang Li; Yu Dong; Dezhen Yang; Wei Xu; Shan Zhang (Acta Neurologica Belgica, 2023)

Recycling of water treatment sludge in concrete: The role of water-binder ratio from a nanoscale perspective - Zhi-Hai He; Xu-Dong Han; Jia-xu Jin; Jiang-shan Li; Wei Tang; Jin-yan Shi (Science of The Total Environment, 2023)

Vulnerability of farmers and herdsmen households in Inner Mongolian plateau to arid climate disasters and their development model - Wenlong Li; Suocheng Dong; Haiying Lin; Fujia Li; Hao Cheng; Zhuang Jin; Shan Wang; Hasbaggen Zhang; Pengshen Hou; Bing Xia (Journal of Cleaner Production, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Experimental investigation and numerical modelling of the seismic performance of corroded T-shaped reinforced concrete shear walls - Lu Yang; Shan-Suo Zheng; Yue Zheng; Li-Guo Dong; Hong-Lin Wu (Engineering Structures, 2023)

Physicochemical and pozzolanic properties of municipal solid waste incineration fly ash with different pretreatments - Zhen Chen; Jiang-Shan Li; Chi-Sun Poon; Wen-Hao Jiang; Zi-Han Ma; Xin Chen; Jian-Xin Lu; Hao-Xin Dong (Waste Management, 2023)

Genetic structure, major chemical component contents and agronomic characters of the principal cultivars of the kelp Saccharina japonica in the largest kelp production province in China - Xiao Dong Li; Chen Hui Zhong; Zhen Hui Jin; Qi Lin; Ti Feng Shan; Shao Jun Pang (Journal of Applied Phycology, 2023)

Rapid prediction models for 3D geometry of landslide dam considering the damming process - Hao Wu; Ting-kai Nian; Zhi-gang Shan; Dong-yang Li; Xing-sen Guo; Xian-gang Jiang (Journal of Mountain Science, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Study of the fracture instability and fault slip risk of overlying strata during mining near faults - Renliang Shan; Dong Liu; Hailong Wang; Xiao Tong; Zhaolong Li; Yan Zhao (Bulletin of Engineering Geology and the Environment, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

An ellipsoid modelling method for discrete element simulation of wheat seeds - Caiyun Lu; Zhen Gao; Hongwen Li; Jin He; Qingjie Wang; Xuyang Wei; Xiuhong Wang; Shan Jiang; Jing Xu; Dong He; Yunxiang Li (Biosystems Engineering, 2023)

Understanding inter-individual variability in short-chain chlorinated paraffin concentrations in human blood - Shan Niu; Xi Chen; Ruiwen Chen; Yun Zou; ZhiZhen Zhang; Li Li; Kimberly J. Hageman; Carla Ng; Liang Dong (Journal of Hazardous Materials, 2023)

Biofilm microenvironment response nanoplatform synergistically degrades biofilm structure and relieves hypoxia for efficient sonodynamic therapy - Heng Dong; Weijun Xiu; Ling Wan; Qiang Li; Yu Zhang; Meng Ding; Jingyang Shan; Kaili Yang; Zhaogang Teng; Lihui Yuwen; Yongbin Mou (Chemical Engineering Journal, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

The accumulation of organic contaminants in hair with different biological characteristics - Bin Tang; Jing Zheng; Shi-Mao Xiong; Feng-Shan Cai; Min Li; Yan Ma; Bo Gao; Dong-Wei Du; Yun-Jiang Yu; Bi-Xian Mai (Chemosphere, 2023)

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

Prediction of Operation Time of Container Ship at Berth under Uncertain Factors Based on a Hybrid Model Combining PCA and ELM Optimized by IPSO - Zhaohui Li; Lin Wang; Wenjia Piao; Hao Jia; Shan Dong; Jiehan Zhang (Journal of Marine Science and Engineering, 2022)
With the rapid development of global trade, the turnover of shipping containers has increased rapidly. How to use port resources reasonably and efficiently has become one of the main challenges that ports need to deal with when planning for the future. In order to develop scientific and efficient berth plans to improve operational efficiency and service level, this paper proposes a hybrid prediction model based on Principal Component Analysis (PCA) and Extreme Learning Machine (ELM) optimized by Improved Particle Swarm Optimization (IPSO), namely, the PCA-IPSO-ELM model. After assessing the uncertain factors influencing the operation time of the container ship at berth, this work reduces the dimensionality of the investigational data by the PCA method. Aiming to solve easy premature convergence of the traditional particle swarm algorithm, this paper introduces an improved particle swarm optimization algorithm via dynamic adjustment of nonlinear parameters. This improved particle swarm algorithm is mainly used to optimize the weights and thresholds of the extreme learning machine. Thus, a PCA-IPSO-ELM model which aims to forecast the operation time of a container ship at berth, is constructed. Using the historical operation data of the Tianjin Port Container Shipping Company as the prediction sample, this PCA-IPSO-ELM model is compared and assessed with traditional models. The results show that compared with other models, the PCA-IPSO-ELM prediction model has the characteristics of high prediction accuracy, fast running rate and strong stability, and it has a higher coefficient of determination and a better fitting degree.

Effects of plant morphology, vitamin C, and other co-present pesticides on the deposition, dissipation, and metabolism of chlorothalonil in pakchoi - Guolei Shan; Meiqing Zhu; Dong Zhang; Taozhong Shi; Jialong Song; Qing X. Li; Rimao Hua (Environmental Science and Pollution Research, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Genomic prediction of drought tolerance during seedling stage in maize using low-cost molecular markers - Ao Zhang; Shan Chen; Zhenhai Cui; Yubo Liu; Yuan Guan; Shuang Yang; Jingtao Qu; Juchao Nie; Dongdong Dang; Cong Li; Xiaomei Dong; Jinjuan Fan; et al. (Euphytica, 2022)
Drought tolerance in maize is a complex and polygenic trait, especially in the seedling stage. In plant breeding, complex genetic traits can be improved by genomic selection (GS), which has become a practical and effective breeding tool. In the present study, a natural maize population named Northeast China core population (NCCP) consisting of 379 inbred lines were genotyped with diversity arrays technology (DArT) and genotyping-by-sequencing (GBS) platforms. Target traits of seedling emergence rate (ER), seedling plant height (SPH), and grain yield (GY) were evaluated under two natural drought stress environments in northeast China. Adequate genetic variations were observed for all the target traits, but they were divergent across environments. Similarly, the heritability of the target trait also varied across years and environments, the heritabilities in 2019 (0.88, 0.82, 0.85 for ER, SPH, GY) were higher than those in 2020 (0.65, 0.53, 0.33) and cross-2-years (0.32, 0.26, 0.33). In total, three marker datasets, 11,865 SilicoDArT markers obtained from the DArT-seq platform, 7837 SNPs obtained from the DArT-seq platform, and 91,003 SNPs obtained from the GBS platform, were used for GS analysis after quality control. The results of phylogenetic trees showed that broad genetic diversity existed in the NCCP population. Genomic prediction results showed that the average prediction accuracies estimated using the DArT SNP dataset under the two-fold cross-validation scheme were 0.27, 0.19, and 0.33, for ER, SPH, and GY, respectively. The result of SilicoDArT is close to the SNPs from DArT-seq, those were 0.26, 0.22, and 0.33. For the trait with lower heritability, the prediction accuracy can be improved using the dataset filtered by linkage disequilibrium. For the same trait, the prediction accuracies estimated with two DArT marker datasets were consistently higher than that estimated with the GBS SNP dataset under the same genotyping cost. The prediction accuracy was improved by controlling population structure and marker quality, even though the marker density was reduced. The prediction accuracies were improved by more than 30% using the significant-associated SNPs. Due to the complexity of drought tolerance under the natural stress environments, multiple years of data need to be accumulated to improve prediction accuracy by reducing genotype-by-environment interaction. Modeling genotype-by-environment interaction into genomic prediction needs to be further developed for improving drought tolerance in maize. The results obtained from the present study provides valuable pathway for improving drought tolerance in maize using GS.

Influence of nitrogen wet deposition on nitrogen output in a typical watershed in the Three Gorges Reservoir Area - Chen-dong Lu; Liu-yi Zhang; Kun Yan; Yu-kuan Wang; Shan-gao Xiong; Chen-tao Huang; Ting-zhen Li; Mao-fei Ni (Journal of Mountain Science, 2022)

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

Attribution of the seasonality of atmospheric heating changes over the western tropical Pacific with a focus on the spring season - Shuheng Lin; Song Yang; Shan He; Zhenning Li; Jiaxin Chen; Wenjie Dong; Jiaxue Wu (Climate Dynamics, 2022)
Atmospheric diabatic heating, a major driving force of atmospheric circulation over the tropics, is strongly confined to the tropical western North Pacific (TWNP) region, with the global warmest sea surface temperature (SST). The changes in diabatic heating over the TWNP, which exert great impacts on the global climate system, have recently exhibited a noticeable seasonal dependence with a remarkable increase in boreal spring. In this study, we applied observations, reanalysis data, and numerical experiments to investigate the causes of the seasonality in heating changes. Results show that in boreal spring convection is more sensitive to the TWNP SST, leading to a more significant enhancement of deep convection, although the increase in the SST is nearly the same as that in the other seasons. In the non-spring seasons, the enhanced convection due to increased local SST is suppressed by the anomalous anticyclonic wind shear over the TWNP, generated by the easterly wind anomalies induced by the tropical Indian Ocean (TIO) warming via the Kevin waves. However, the TIO warming does not show any suppressing effect in spring because it is much weaker than that in the other seasons and thus the warming itself cannot induce sufficient convective heating anomalies to excite the Kelvin waves.

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

SSR Marker-Based Genetic Resource Assessment of the Rainbow Clam Moerella iridescens Along the Coasts of China: Implications for Strategy of Conservation Management - Xiaoying Li; Shan Gao; Manman Zhao; Zhiguo Dong (Frontiers in Marine Science, 2022)
This study aims to determine the genetic structure of rainbow clam Moerella iridescens in different sea areas of China. Seventeen pairs of microsatellite primers (SSR) were used to amplify the SSRs of rainbow clam in Lianyungang of Haizhou Bay, Chongming of Shanghai, Ningde of Fujian, Daishan of Zhoushan, and Cixi and Wenzhou of Zhejiang. A total of 1,146 alleles were detected in 310 individuals from the 17 SSR loci. The average observed heterozygosity of six populations was 0.4381−0.6139, the average expected heterozygosity was 0.5897−0.7325, and the average Shannon diversity index was 1.2655−1.7998. The clams exhibited rich genetic diversity, and the F ST of the genetic differentiation index of the six populations was 0.0470, indicating low genetic differentiation among the populations. The results indicated that rainbow clams along the coasts of China exhibited high diversity and low population differentiation.

Effects of temperature, moisture, substrates and soil coverage on sclerotium germination and hyphal growth of Southern blight of apple in China - Xiang-li Dong; Chang-yan Gao; Ping-liang Li; Sen Lian; Shan-yue Zhou; Bao-hua Li (European Journal of Plant Pathology, 2022)

Deinococcus aestuarii sp. nov. and Deinococcus aquaedulcis sp. nov., two novel resistant bacteria isolated from pearl river estuary - Ling-Zi Yin; Jia-Ling Li; Ze-Tao Liu; Bao-Zhu Fang; Pandeng Wang; Xiao-Qing Luo; Lei Dong; Li Duan; Shan-Hui Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Evaluation of Rainfall Forecasts by Three Mesoscale Models during the Mei-yu Season of 2008 in Taiwan. Part I: Subjective Comparison - Sahana Paul; Chung-Chieh Wang; Li-Shan Tseng; Dong-In Lee; Jing-Shan Hong; Tzay-Ming Leou (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Study on synthesis and anticancer activity of 17beta-estradiol-phenol/aniline nitrogen mustard derivatives - Yu-dong Yin; Jing-jing Liu; Wen-fei Liao; Xian-kun Guo; Li-shan Zhang; Wei-bin Mo; Ke-guang Cheng (Medicinal Chemistry Research, 2021)

Plant Polyphenols: Potential Antidotes for Lead Exposure - Ying Li; Hao Lv; Chenyu Xue; Na Dong; Chongpeng Bi; Anshan Shan (Biological Trace Element Research, 2021)

Formyl tetrahydrofolate deformylase affects hydrogen peroxide accumulation and leaf senescence by regulating the folate status and redox homeostasis in rice - Erhui Xiong; Guojun Dong; Fei Chen; Chen Zhang; Shan Li; Yanli Zhang; Jahidul Islam Shohag; Xiaoe Yang; Yihua Zhou; Qian Qian; Limin Wu; Yanchun Yu (Science China Life Sciences, 2021)

TRAK1-Mediated Abnormality of Mitochondrial Fission Increases Seizure Susceptibility in Temporal Lobe Epilepsy - Hao Wu; Yong Liu; Huanfa Li; Changwang Du; Kuo Li; Shan Dong; Qiang Meng; Hua Zhang (Molecular Neurobiology, 2021)

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

Dynamic network connectivity predicts subjective cognitive decline: the Sino-Longitudinal Cognitive impairment and dementia study - Guozhao Dong; Liu Yang; Chiang-shan R. Li; Xiaoni Wang; Yihe Zhang; Wenying Du; Ying Han; Xiaoying Tang (Brain Imaging and Behavior, 2020)

Simulation and verification of an air-gun array wavelet in time-frequency domain based on van der waals gas equation - Dong Zhang; Huai-shan Liu; Lei Xing; Qian-qian Li; Xue-qin Liu; Jia Wei; Jian-hua Wang; Heng Zhou; Xin-min Ge (Applied Geophysics, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Association between long-term exposure to Sulfur dioxide pollution and hypertension incidence in northern China: a 12-year cohort study - Mengfan Yan; Chaokang Li; Liwen Zhang; Xi Chen; Xueli Yang; Anqi Shan; Xuejun Li; Hui Wu; Zhao Ma; Yu Zhang; Pengyi Guo; Guanghui Dong; et al. (Environmental Science and Pollution Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Difference of planktonic ciliate communities of the tropical West Pacific, the Bering Sea and the Arctic Ocean - Chaofeng Wang; Haibo Li; Zhiqiang Xu; Shan Zheng; Qiang Hao; Yi Dong; Li Zhao; Wuchang Zhang; Yuan Zhao; Gérald Grégori; Tian Xiao (Acta Oceanologica Sinica, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

Identification of soybean drought-tolerant genotypes and loci correlated with agronomic traits contributes new candidate genes for breeding - Limiao Chen; Yisheng Fang; Xiangyong Li; Kai Zeng; Haifeng Chen; Hengbin Zhang; Hongli Yang; Dong Cao; Qingnan Hao; Songli Yuan; Chanjuan Zhang; Wei Guo; et al. (Plant Molecular Biology, 2020)

Microaerobic Fe(II) oxidation coupled to carbon assimilation processes driven by microbes from paddy soil - Xiaomin Li; Shan Mou; Yating Chen; Tongxu Liu; Jun Dong; Fangbai Li (Science China Earth Sciences, 2019)

FvC5SD overexpression enhances drought tolerance in soybean by reactive oxygen species scavenging and modulating stress-responsive gene expression - Ling Zhang; Tong Li; Yang Wang; Yuanyu Zhang; Ying-shan Dong (Plant Cell Reports, 2019)

A geostatistic investigation of the comprehensive evaluation of fertility and spatial heterogeneity of forest soil nutrients in hilly and mountainous regions of southern China - Da-ping Song; Hong Li; Shan-jiang Liu; Guo-yuan Zou; Dong-sheng Liu (Arabian Journal of Geosciences, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Polyphenolic compounds from Malus hupehensis and their free radical scavenging effects - Qingwen Hu; Ying-Ying Chen; Qi-Yang Jiao; Afsar Khan; Jimiao Shan; Gui-Dong Cao; Feng Li; Chao Zhang; Hong-Xiang Lou (Natural Product Research, 2018)

A revisit to fishmeal usage and associated consequences in Chinese aquaculture - Dong Han; Xiujuan Shan; Wenbing Zhang; Yushun Chen; Qingyin Wang; Zhongjie Li; Guofan Zhang; Pao Xu; Jiale Li; Shouqi Xie; Kangsen Mai; Qisheng Tang; et al. (Reviews in Aquaculture, 2018)
China has dominated global aquaculture production for more than two decades. Aquaculture production in China increased from 24.6 million metric tons (mmt) in 2000 to 47.5 mmt in 2014, an increment of 93.1%. Along with the fast‐growing aquaculture industry, aquafeed production in China increased from 5.1 mmt in 2000 to 19.0 mmt in 2014, an increment of 272.5%. However, despite the rapid increase in aquafeed production, the fishmeal usage in aquafeeds in China has remained stable over the years. Fishmeal imports into China remained relatively steady at 1.0–1.5 mmt per annum from 2000 to 2014. An often unacknowledged fact is that China contributes more than 60% to the world aquaculture production at a cost of only 25–30% of the world fishmeal output. This review attempts to explain why the fishmeal usage has not increased proportionately with the increasing aquafeed production in China from several angles: (i) the current status of fishmeal usage in Chinese aquaculture; (ii) the relationship between the decreasing dietary inclusions of fishmeal and improved feed techniques, especially the use of alternative protein sources for fishmeal; (iii) the dominance of Chinese aquaculture by low trophic level species of plants, filter feeders, herbivores and omnivores and consequent low demands for fishmeal; and (iv) the increasing price of fishmeal and the management of exploitation of wild fisheries in the main fishmeal exporting countries to China. The trends and prospects of fishmeal usage in the future in Chinese aquaculture and the associated consequences are also addressed. Like other countries, China is now actively developing both resource conservation‐based capture fisheries and environment‐friendly freshwater and marine aquaculture systems. Aquaculture will be the main source of aquatic food in the future and will also indirectly contribute to save the world wild fisheries, and China will be main player that will continue to contribute towards this end.

The effect of substrate media on the survival and growth of the eelgrass Zostera marina - Qiang Xu; Pei-Dong Zhang; Yan-Shan Liu; Xi-Tao Wang; Wen-Tao Li (Marine Biology Research, 2018)

Differences in planktonic ciliate spatial distribution in spring and autumn in the southern Yellow Sea - Shan Zhang; Haibo Li; Xue Chen; Yi Dong; Fang Zhang; Tian Xiao; Wuchang Zhang; Yuan Zhao (Acta Oceanologica Sinica, 2018)

A study of variation characteristics of Gobi broadband emissivity based on field observational experiments in northwestern China - Zhi-yuan Zheng; Zhi-gang Wei; Zhi-ping Wen; Wen-jie Dong; Zhen-chao Li; Xiao-hang Wen; Xian Zhu; Chen Chen; Shan-shan Hu (Theoretical and Applied Climatology, 2018)

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Two novel bocaparvovirus species identified in wild Himalayan marmots - Yuanyun Ao; Xiaoyue Li; Lili Li; Xiaolu Xie; Dong Jin; Jiemei Yu; Shan Lu; Zhaojun Duan (Science China Life Sciences, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Characterization and physical mapping of nuclear ribosomal RNA (rRNA) genes in the haploid gametophytes of Saccharina japonica (Phaeophyta) - Li Liu; Qi-Fan Yang; Wu-Shan Dong; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

The influence of increased iron concentration on survival and growth of seedlings and young plants of eelgrass Zostera marina - Xi‐Tao Wang; Qian Zhang; Yan‐Shan Liu; Pei‐Dong Zhang; Wen‐Tao Li (Marine Ecology, 2017)
Iron (Fe) is an essential nutrient for plants but toxic at high concentrations. We subjected seedlings and young plants of eelgrass Zostera marina to different seawater iron concentrations (500, 600, 700, 800, 1,000 and 1,500 μg/L) for 30 days under controlled laboratory conditions. Natural seawater without added iron (500 μg/L) was used as reference seawater. No sediments were provided to avoid iron scavenging by particle surfaces in the sediment. We measured plant response in terms of survivorship, morphology, growth rate and productivity. Survival analysis combined with morphological, dynamic and productive assessment suggested that the optimum seawater iron concentration for the establishment of Z. marina seedlings and young plants is 700 μg/L. The no observed effect concentration, lowest observed effect concentration, lethal concentration that caused an increase in mortality to 10% of that of the control, and the effect concentration that caused a decrease in growth to 10% of that of the control values of young plants were significantly lower than those of seedlings, implying an increased sensitivity to high Fe concentrations (>1,000 μg/L). This study further develops our understanding of the physiological ecology of the early life stages of Z. marina and provides data that could prove helpful in the development of successful eelgrass restoration and conservation.

A new androstanoid metabolite from a soil fungus Curvularia borreriae strain HS-FG-237 - Li-Fei Liu; Hui Zhang; Huan Qi; Xiao-Ming Wang; Ji-Dong Wang; Gui-Shan Tan (Natural Product Research, 2017)

Deinococcus malanensis sp. nov., isolated from radiation-polluted soil - Jing Zhu; Shan-Hui Li; Qi-Yong Tang; Min Chu; Wei Wang; Nimaichand Salam; Li Li; Wael N. Hozzein; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2017)

Occurrence of viruses infecting melon in Xinjiang of China and molecular characterization of Watermelon mosaic virus isolates - Dong Wang; Guan Li; Shan Shan Du (European Journal of Plant Pathology, 2017)

Identification of aberrant DNA methylation involved in chemoradiation-resistant HCT116 cells via methylation-specific microarray - Wei Xiong; Yun-Feng Li; Shan Liu; Ting Chen; Hong-Tao Zhang; Zhi-Bin Yang; Ying-Ying Ding; De-Pei Gao; Guan-Shun Wang; Jian Dong (Molecular & Cellular Toxicology, 2016)

Common Polymorphisms Within QPCT Gene Are Associated with the Susceptibility of Schizophrenia in a Han Chinese Population - Qiao-Quan Zhang; Teng Jiang; Li-Ze Gu; Xi-Chen Zhu; Hong-Dong Zhao; Qing Gao; Hai-Qing Zhu; Jun-Shan Zhou; Ying-Dong Zhang (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2016)

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

Endothelin-1 increases melanin synthesis in an established sheep skin melanocyte culture - Yamiao Pang; Jianjun Geng; Yilong Qin; Haidong Wang; Ruiwen Fan; Ying Zhang; Hongquan Li; Shan Jiang; Changsheng Dong (In Vitro Cellular & Developmental Biology - Animal, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

miR-26a suppresses EMT by disrupting the Lin28B/let-7d axis: potential cross-talks among miRNAs in IPF - Haihai Liang; Shanshan Liu; Yang Chen; Xue Bai; Li Liu; Yuechao Dong; Meiyu Hu; Xiaomin Su; Yingzhun Chen; Longtao Huangfu; Xuelian Li; Yunyan Gu; et al. (Journal of Molecular Medicine, 2016)

Two new abietane diterpenoid glycosides from Clinopodium chinense - Yin-Di Zhu; Jing-Yi Zhang; Peng-Fei Li; Hai-Feng Wu; Nai-Liang Zhu; Hai Jiang; Cui-Yan Lv; Li-Li Wu; Ze-Xin Ma; Xu-Dong Xu; Guo-Xu Ma; Jun-Shan Yang (Natural Product Research, 2016)

Altered Expression Pattern of Acid-Sensing Ion Channel Isoforms in Piriform Cortex After Seizures - Hao Wu; Chao Wang; Bei Liu; Huanfa Li; Yu Zhang; Shan Dong; Guodong Gao; Hua Zhang (Molecular Neurobiology, 2016)

A new sesquiterpenoid quinone with cytotoxicity from Abelmoschus sagittifolius - De-Li Chen; Xiao-Po Zhang; Guo-Xu Ma; Hai-Feng Wu; Jun-Shan Yang; Xu-Dong Xu (Natural Product Research, 2016)

Landslide monitoring in southwestern China via time-lapse electrical resistivity tomography - Dong Xu; Xiang-Yun Hu; Chun-Ling Shan; Rui-Heng Li (Applied Geophysics, 2016)

New cytotoxic lignan glycosides from Phyllanthus glaucus - Shan Yu; Jun-Jiang Lv; Jian-Qiang Zhao; Yan Li; Dong Wang; Chong-Ren Yang; Min Xu; Ying-Jun Zhang (Natural Product Research, 2016)

RETRACTED ARTICLE: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

A New Detection Method of Volcanic Ash Cloud Based on MODIS Image - Jing-Yuan Yin; Jiang-Shan Dong; Cheng-Fan Li; Jun-Juan Zhao (Journal of the Indian Society of Remote Sensing, 2015)

Paenibacillus wulumuqiensis sp. nov. and Paenibacillus dauci sp. nov., two novel species of the genus Paenibacillus - Jing Zhu; Wei Wang; Shan-Hui Li; Su-Qin Song; Yu-Qing Xie; Qi-Yong Tang; Ghenijan Osman; Yu-Hu Shi; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Bone morphogenetic protein-4 induces upregulation of Cav3.1 Ca2+ channels in HL-1 atrial myocytes - Chao-Wei Hu; Qi Li; Ying Zhang; Yu-Hong Li; Hong-Chao Jiang; Ming-Yu Liu; Shan-Liang Li; Wei Han; De-Li Dong (Pflügers Archiv - European Journal of Physiology, 2014)

Monitoring of urban heat island in Shanghai, China, from 1981 to 2010 with satellite data - Cheng-fan Li; Di Shen; Jiang-shan Dong; Jing-yuan Yin; Jun-juan Zhao; Dan Xue (Arabian Journal of Geosciences, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Genistein Alleviates Radiation-Induced Pneumonitis by Depressing Ape1/Ref-1 Expression to Down-regulate Inflammatory Cytokines - Guo-Dong Liu; Lei Xia; Jian-Wu Zhu; Shan Ou; Meng-Xia Li; Yong He; Wei Luo; Juan Li; Qian Zhou; Xue-Qin Yang; Jin-Lu Shan; Ge Wang; et al. (Cell Biochemistry and Biophysics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Geochemistry of magmatic and hydrothermal zircon from the highly evolved Baerzhe alkaline granite: implications for Zr–REE–Nb mineralization - Wu-Bin Yang; He-Cai Niu; Qiang Shan; Wei-Dong Sun; Hong Zhang; Ning-Bo Li; Yu-Hang Jiang; Xue-Yuan Yu (Mineralium Deposita, 2014)

Improved yield and Zn accumulation for rice grain by Zn fertilization and optimized water management - Yu-yan Wang; Yan-yan Wei; Lan-xue Dong; Ling-li Lu; Ying Feng; Jie Zhang; Feng-shan Pan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Distribution of Polychlorinated Biphenyls in Soil Around Three Typical Industrial Sites in Beijing, China - Yong-Fei Zhang; Shan Fu; Yuan Dong; Hai-Feng Nie; Zheng Li; Xin-Chun Liu (Bulletin of Environmental Contamination and Toxicology, 2014)

Systematic expression analysis of genes related to multidrug-resistance in isogenic docetaxel- and adriamycin-resistant breast cancer cell lines - Wen-Jing Li; Shan-Liang Zhong; Yuan-Jian Wu; Wei-Dong Xu; Jin-Jin Xu; Jin-Hai Tang; Jian-Hua Zhao (Molecular Biology Reports, 2013)

Endoscopic ultrasonographic features of gastric linitis plastica in fifty-five Chinese patients - Guo-dong Shan; Guo-qiang Xu; You-ming Li (Journal of Zhejiang University-SCIENCE B, 2013)

Two new diterpenes from Caesalpinia minax Hance - Guo-Xu Ma; Jing-Quan Yuan; Li Cao; Jun-Shan Yang; Xu-Dong Xu (Natural Product Research, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

A new flavonol from Oxytropis ochrocephala Bunge - Xia Li; Shou-De Zhang; Hui-Zi Jin; Feng Dong; Lei Shan; Wei-Dong Zhang (Natural Product Research, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Effect of home processing on the distribution and reduction of pesticide residues in apples - Z. Kong; W. Shan; F. Dong; X. Liu; J. Xu; M. Li; Y. Zheng (Food Additives & Contaminants: Part A, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Genetic Structure Within and Among Populations of Saruma henryi, an Endangered Plant Endemic to China - Tian-Hua Zhou; Shan-Shan Dong; Shan Li; Gui-Fang Zhao (Biochemical Genetics, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Effects of exogenous hydrogen sulfide on the ascorbate and glutathione metabolism in wheat seedlings leaves under water stress - Chang-juan Shan; Sheng-li Zhang; Dong-fang Li; Yuan-zeng Zhao; Xue-liang Tian; Xin-liang Zhao; Ying-xia Wu; Xiu-ying Wei; Run-qiang Liu (Acta Physiologiae Plantarum, 2011)

A new iridoid compound from Patrinia rupestris (Pall.) Juss. - Dong-Feng Qiu; Xiu-Ping Yang; Yang-Jun Xu; Xiao-Qing Liu; Hong-Li Liu; Cheng-Shan Yuan (Natural Product Research, 2011)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Acetylcholine prevents angiotensin II-induced oxidative stress and apoptosis in H9c2 cells - Jin-Jun Liu; Dong-Ling Li; Juan Zhou; Lei Sun; Ming Zhao; Shan-Shan Kong; You-Hua Wang; Xiao-Jiang Yu; Jun Zhou; Wei-Jin Zang (Apoptosis, 2011)

RA induces the neural-like cells generated from epigenetic modified NIH/3T3 cells - Xi-Mei Zhang; Qiu-Ming Li; Dong-Ju Su; Ning Wang; Zhi-Yan Shan; Lian-Hong Jin; Lei Lei (Molecular Biology Reports, 2010)

Isolation and characterization of 14 dinucleotide microsatellite loci in the endangered herb Saruma henryi Oliv. (Aristolochiaceae) - Shan-Shan Dong; Xuan Huang; Zeng-Qiang Qian; Tian-Hua Zhou; Shan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2009)

Wavelet analysis and nonparametric test for climate change in Tarim River Basin of Xinjiang during 1959–2006 - Jianhua Xu; Yaning Chen; Weihong Li; Minhe Ji; Shan Dong; Yulian Hong (Chinese Geographical Science, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Serum Zinc, Copper, and Zinc/Copper in Healthy Residents of Jinan - Hong-qun Zhang; Ning Li; Zheng Zhang; Shan Gao; Hong-yin Yin; Dong-mei Guo; Xibao Gao (Biological Trace Element Research, 2009)

Inducible Expression of Functional Mu Opioid Receptors in Murine Dendritic Cells - Zheng-Hong Li; Niansheng Chu; Li-Dong Shan; Shan Gong; Qi-Zhang Yin; Xing-Hong Jiang (Journal of Neuroimmune Pharmacology, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Damage and conservation of the high cliff on the Northern area of Dunhuang Mogao Grottoes, China - Qing-lin Guo; Xu-dong Wang; Hu-yuan Zhang; Zui-xiong Li; Shan-long Yang (Landslides, 2009)

The complex nonlinear systems with fractal as well as chaotic dynamics of annual runoff processes in the three headwaters of the Tarim River - Jianhua Xu; Yaning Chen; Weihong Li; Minhe Ji; Shan Dong (Journal of Geographical Sciences, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

The value of endoscopic ultrasonography on diagnosis and treatment of esophageal hamartoma - Guo-qiang Xu; Feng-ling Hu; Li-hua Chen; Guo-dong Shan; Bing-ling Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Long-term trend and fractal of annual runoff process in mainstream of Tarim River - Jianhua Xu; Yaning Chen; Weihong Li; Shan Dong (Chinese Geographical Science, 2008)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)